Gamma-Ray Binaries Revealed - Mirabel Miquele, Igor Felix (2012)
Recent ground- and space-based telescopes that detect high-energy photons from a few up to hundreds of gigaelectron volts (GeV) have opened a new window on the universe. However, because of the relatively poor angular resolution of these telescopes, a large fraction of the thousands of sources of gamma rays observed remains unknown. Compact astrophysical objects are among those high-energy sources, and in the Milky Way there is a particular class called gamma-ray binaries. These are neutron stars or black holes orbiting around massive stars (1). On page 189 of this issue, the Fermi Large Area Telescope Collaboration (2) use the correlated orbital modulation at gamma-ray, x-ray, and radiowave wavelengths to show that the source 1FGL J1018.6-5856 is a new gamma-ray binary, demonstrating the potential of searches for periodic modulation at gamma rays and other wavelengths to unveil new populations of gamma-ray binaries.